Mangrove Capability as Natural Coastal Defense Using Remote Sensing and GIS Assessment - Abdul Aziz, Amirul Afif (IRC, 2016)
Mangrove forest become a hot topic being discuss among research and being acknowledge as a natural costal protection after the Tsunami tragedy back in 2004. Mangrove not only able to decelerate wave before it hit coastline area to protect from hurricanes, typhoons and other ocean related. It also create a suitable habitat for fishes and other marine life which result in great value to coastal nations